PENGARUH WAKTU INOKULASI PEANUT STRIPE VIRUS (PSTV) TERHADAP HASIL PRODUKSI BEBERAPA VARIETAS TANAMAN KEDELAI (Glycine Max L) - Mujoko, Tri; Suryaminarsih, Penta; Jati Laksono, Roy (MAPETA, 2000)
The research was conducted to know time inoculation effect of Peanut Stripe Virus on some soybean varieties. The research has been carried out at UPN "veteran" green house and aranged with Factorial Ramdomize Complate Block Design. The factors were time inoculation (2, 3, 4 weeks after panting and control without inoculation) and soybean varieties (Argomulyo, Bromo and Kawi) with three-replicauons. The result of the research showed that two week after planting inoculation incubation periode was 13 day after inoculation. Bromo varieties was heigiest on damage intensity and yield (34,50 grl plant) so bromo called resistance vaneties.